The Public Relations and Gender Equality in Nigeria: Assessing Representation and Its Impact on Social Change - Tanyishi, Ahyenopwa Elmond (African Journal of Stability and Development (AJSD), 2025)
This study examined the role of public relations in shaping gender representation and influencing social change in Nigeria. It explored how PR campaigns have historically framed gender roles and assessed their contribution to either reinforcing or challenging existing stereotypes. Given the significant influence of PR in shaping public discourse, the study sought to determine PR’s effectiveness in promoting gender equality through advocacy, awareness, and policy engagement. A qualitative research approach was adopted, relying on secondary data sources such as PR campaigns, media reports, corporate publications, policy documents, and NGO reports. Thematic analysis was conducted to identify recurring patterns in gender-focused PR messaging and strategies. Findings revealed that while traditional PR narratives in Nigeria often reinforced patriarchal norms by portraying women in subordinate roles, contemporary PR efforts have increasingly promoted gender inclusivity. However, cultural, political, and economic factors continue to shape the effectiveness of PR-driven gender advocacy, with corporate and governmental PR campaigns sometimes lacking sustained commitment to genuine change. The study concluded that PR could serve as a powerful tool for advancing gender equality if strategic, gender-sensitive communication practices are prioritised. It recommended policy-driven PR initiatives, stronger advocacy collaborations, and research-driven messaging to ensure meaningful and sustainable progress in gender representation.